Experimental investigation of the dynamic characteristics of vertical clamped free cylindrical shell. - Lejano, Bernardo A. (Philippine Engineering Journal)
An experimental procedure ws developed to investigate the dynamic characteristics of vertical clamped free cylindrical shell. A cylindrical shell model made of rubber was constructed and tested in the dynamics laboratory of the Integrated Research and Training Center (IRTC), Technological University of the Philippines (TUP). Forced vibratino tests were conducted using a shaking table while free vibration was accomplished by applying an initial displacement. The experimentally obtained dynamic characteristics show good agreement with the results using the finite element method.